Perception of Secondary School Teachers Towards the Transformational Leadership for Teachers' Effectiveness - Hamid, Zainab Bibi (1998)
The main aim of this study was to identify the perception of secondary school teachers towards transformational leadership styles among their principals for teachers' effectiveness. The transformational leadership factors consist of idealised influence attribute and behaviour, intellectual stimulation, individualised consideration and inspirational motivation. The study was conducted in ten secondary schools in the Kuala Pilah, Jelebu and Jempol district. A total of 235 teachers were selected by using a simple random sampling method. Statistical analysis such as descriptive, percentage, means scores and Pearson correlation test were carried out. The findings revealed that the principals 'sometimes' exhibited idealised influence attribute (X = 2.35) and behaviour, 'sometimes' provided inspirational motivation (X=2.59), and 'sometimes' (X=2.59) utilised intellectual stimulation in executing tasks to teachers. The results also proved principals in KPJJ district 'once in a while' give individualised consideration (X= 1.89) to their teachers. Correlational analysis indicated that principals' idealised influence attribute, idealised influence behaviour, inspirational motivation, intellectual stimulation and individualised consideration were related to teachers' effectiveness. This means that the relationship between the four factors of transformational leadership and teachers' effectiveness were positive and moderate. The higher the principals displayed transformational leadership styles the higher will be teachers' effectiveness in their performance.